Pengembangan dan Evaluasi Usabilitas Gim Edukasi Bahasa Jawa Menggunakan Game Development Life Cycle - M. Da’il Falah; Chanifah Indah Ratnasari (TIN: Terapan Informatika Nusantara, 2026)
Javanese is a regional language that should be introduced from elementary school because it represents cultural values, local identity, and Javanese manners. This study aims to design, develop, and evaluate the usability of an Android-based Javanese learning game using the Game Development Life Cycle (GDLC). The study was conducted at SDN Candirejo by involving the school principal as an interview informant and 15 students from grades III, IV, and V as respondents. The game content was prepared with reference to the Remen Basa Jawi 2013 Curriculum textbooks for grades I to VI and input from the school. The game applies the Drill and Practice method in an adventure puzzle format through area exploration, vocabulary collection, practice questions, a dictionary, inventory, and boss-stage evaluation. The content covers daily vocabulary, the use of Ngoko and Krama, identification of mixed-language sentences, and language selection based on the interlocutor. Alpha testing using Black Box Testing showed that all 16 scenarios worked as expected, with a success rate of 100%. Beta testing using the System Usability Scale (SUS) produced an average score of 72.17, which falls into the Acceptable category with a Good rating. These findings indicate that the game has good usability and can be considered an alternative medium for supporting Javanese language practice in elementary schools. This study contributes an interactive digital learning medium that integrates vocabulary practice, Ngoko-Krama use, and contextual language selection to support Javanese language preservation in elementary schools.